Strategy for Increasing Motorcycle Patrols to Reduce Crime Rates in Malang City - Ginting, Giovanne Perdana Padang Sambo (Police Studies Review, 2024)
This research aims to evaluate and enhance the effectiveness of motorcycle patrols as a strategy to combat crime in Malang City. Against the backdrop of rising crime rates in the region, the focus of this study is on identifying strategies to increase police presence on the streets through the use of motorcycles for patrol purposes. The objective is to create a more active and responsive police presence to criminal incidents, underpinned by the concept that visible police presence can deter criminal activities. The methodology involves analyzing crime data, assessing patrol needs in various areas, and evaluating the effectiveness of implemented strategies. It is hoped that by optimizing motorcycle patrols, a significant reduction in crime rates can be achieved in Malang City.